Biostatistical analysis of treatment results of bacterial liver abscesses using minimally invasive techniques and open surgery. - A. A. Кipshidze; P. S. Beyner; N. V. Beyner (Medičnì Perspektivi, 2013)
Today bacterial abscesses remain one of the most difficult complications in surgical hepatology, both traditional and minimally invasive methods of their treatment are used. Bio-statistical analysis is used due to the fact that strong evidences are required for the effectiveness of one or another method of surgical intervention. The estimation of statistical significance of differences between the control and the main group of patients with liver abscesses is given in this paper. Depending on the treatment method patients were divided into two groups: 1 - minimally invasive surgery (89 cases); 2 – laporatomy surgery (74 patients). Data comparison was performed by means of Stjudent's criterion. The effectiveness of method of abscesses drainage using interventional sonography, outer nazobiliar drainage with reorganization of ductal liver system and abscess cavity with the help of modern antiseptics was considered. The percentage of cured patients was also estimated.